Anterior View of Postural Youth Behavior: A Case Study - Quka, Najada; Selenica, Rigerta (European Journal of Multidisciplinary Studies, 2022)
In the last two decades, incorrect posture has become significantly more widespread, particularly among school-aged children. According to various studies, scoliosis is one of the most prevalent incorrect postural types seen in school-aged children. The purpose of our study is to find out how common "Scoliosis" is among Albanian children. Methodology: About 308 kids aged 10 to 13 years (n = 151 girls, n = 157 boys) were randomly selected from Tirana public schools for this study. This group took part in a Posture Shape Examination (Anterior View), using Grid Chart Postural Analysis and the platform “Posture Screen Mobile®-PSM” (iPod). To provide exact information on their looks, children were photographed from the front (upright standing posture) wearing as little as possible. We analyzed the data statistically using "IBM SPSS Statistics 20," which included Descriptive and Frequency Analyze. Results: Our findings revealed that 34 individuals, or 11.03 % of the youngsters, had Scoliosis. This improper posture was more prevalent in 13-year-old youngsters (19.5%) than in children aged 10, 11, or 12. In comparison to females, boys were more impacted by scoliosis (12.7%) than girls (9.3%). The results reveal a minor difference in the degrees of postural displacement between boys (5.81850) and females (5.43610). Furthermore, postural displacement is greater in 13-year-old males (7.76500) and 12-year-old girls (6.14580). Conclusions and Recommendations: Based on the results of our study we conclude that incidents of anterior postural asymmetry occurred even in Albanian school-age children. Scoliosis, even why is detected more in boys, seems to be present in both genders. Based on these conclusions we recommend that parents, teachers, and children should be more informed about good posture and the problems that might arise from an incorrect posture. Further studies are important to be conducted in this field, in order to prevent the occurrence of these deviations and their aggravation in our young generation.
Keywords: Scoliosis, Children, Posture Asymmetry, 10-13 years old, Postural Deviations